EFEKTIVITAS PROGRAM KELUARGA HARAPAN (PKH) DALAM UPAYA PENGENTASAN KEMISKINAN - Enda Novieta, Sujianto, Harapan Tua (Universitas Riau, 2019)
Effectiveness of the Hope Family Program (PKH) in Poverty Alleviation efforts. This study aims to determine the effectiveness of family hope programs (PKH) in poverty alleviation efforts. This type of research is a qualitative descriptive study with a research focus on the accuracy of program targets, program socialization, program objectives and program monitoring. Informants in this study were PKH implementers and PKH beneficiary families. Data collection is done by the method of observation, interviews and documentation. Data analysis using source triangulation method. The results showed that PKH target setting was not yet effective, because from the distribution of PKH beneficiary families there were still families who were able but still getting PKH assistance. However, in the part of PKH's objectives and monitoring, it has been effective, PKH assistance is able to meet the needs of PKH beneficiary families and the assistance process in the form of information, motivation and education is carried out by PKH facilitators in accordance with Permensos No. 1 of 2018 concerning the implementation of PKH.